Prediction Model Based on SVM Augmented Classification for Component Based QoS - Anurag Mishra, Ashish Sharma (International Journal of Advanced Science and Technology, 2020)
As we are observing in change in pattern of how software is being developed and different life cycles of development. It is evident that in the last recent years software are being written and developed in such a different manner in contrast to the former decade. Apart from the software development styles we have also seen rapid innovations in the architectures of the computing machines. Similarly, with the pace of automation and cloud-based application we have seen rapid innovations in the field of Machine learning, Artificial intelligence. These innovative approaches enable the machine to predict the outcomes based on dependable parameters. In general approach is to use the collected dataset to train and test. In this paper we have used dataset which is being donated at PROMISE Repository of Software Engineering.